Comparative Genomic and Sequence Analysis Provides Insight into the Molecular Functionality of NOD1 and NOD2 - Boyle, Joseph; Mayle, Sophie; Parkhouse, Rhainnon; Monie, Tom P. (Frontiers in Immunology, 2013)
Amino acids with functional or key structural roles display higher degrees of conservation through evolution. The comparative analysis of protein sequences from multiple species and/or between homologous proteins can be highly informative in the identification of key structural and functional residues. Residues which in turn provide insight into the molecular mechanisms of protein function. We have explored the genomic and amino acid conservation of the prototypic innate immune genes NOD1 and NOD2. NOD1 orthologs were found in all vertebrate species analysed, whilst NOD2 was absent from the genomes of avian, reptilian and amphibian species. Evolutionary trace analysis was used to identify highly conserved regions of NOD1 and NOD2 across multiple species. Consistent with the known functions of NOD1 and NOD2 highly conserved patches were identified that matched the Walker A and B motifs and provided interaction surfaces for the adaptor protein RIP2. Other patches of high conservation reflect key structural functions as predicted by homology models. In addition, the pattern of residue conservation within the LRR region of NOD1 and NOD2 is indicative of a conserved mechanism of ligand recognition involving the concave surface of the LRRs.